Unity in Diversity: Alleviating The Strains of Mental Illness Through Cohesion, Not Coercion - Washieka, Torres (The Center for Disability Studies and Services Brawijaya University, 2016)
I create a theoretical framework for ways to alleviate the mental health issues that Indonesia faces. My work posits that if disability rights advocates were to try to alleviate this issue from an American perspective, we would not only be attempting to reinforce Western standards of superiority, but we would be, in a way, attempting to colonize and dominate the argument surrounding mental illness services. My argument further suggests that the only way to alleviate any social ill within Indonesia must come from and be invested in by Indonesians. These solutions must be respectful of who the Indonesian people are, their relationship to their families and one another, and their identity. I will look at ways in which Western media provides a narrow scope of how issues surrounding Indonesian mental illness are spread. Furthermore, I will offer possible suggestions in alleviating the mental health issues in Indonesia while keeping in mind that all of these must be done from and with the Indonesian people not by coercion.